Experience of Asian countries in terms of children’s social protection and support. - Aikenova., D. M. (Journal of Oriental Studies, 2016)
The article presents the experience of Asian countries, particularly Singapore, the United Arab Emirates and Malaysia in the field of social protection and support for families with children. These techniques may be useful for implementation in Kazakhstan.